Humanitarian and Social Protection Linkages with Examples from South Asia - Jorgensen, Steen Lau; Ceretti, Maria Virginia (World Bank, Washington, DC, 2022)
Traditionally social protection (SP) and humanitarian programs were quite distinct in their objectives, scope, and operations, but over time those distinctions have diminished and with that the gains from better integration. Humanitarian programs are committed to more involvement of national actors, more use of cash, and greater popular participation all matters that are important for SP actors. On the other side, SP has gradually shifted into shock-responsive or adaptive SP that explicitly targets not only the poor but also those affected by shocks. Beyond presenting the divide and overlap of concepts, principles, and commitments from the SP and humanitarian realms, this paper attempts at unbundling a framework for humanitarian and SP integration across the delivery chain (based on the paper by Seyfert et al. 2019). Global experiences across the integration spectrum, as well as the practical application of the framework in Afghanistan, Bangladesh, and Pakistan, are exemplified. The analysis shows how programs apply a ‘mix and match’ approach building on factors such as political will, technical capacity, and alignment of objectives across implementing agencies, donors, and the government. The paper identifies constraints and opportunities for better integration and proposes a set of actions to enhance benefits for affected populations.